2008
DOI: 10.1128/jb.00715-08
|View full text |Cite
|
Sign up to set email alerts
|

Processing of a Membrane Protein Required for Cell-to-Cell Signaling during Endospore Formation in Bacillus subtilis

Abstract: Activation of the late prespore-specific RNA polymerase sigma factor G during Bacillus subtilis sporulation coincides with completion of the engulfment process, when the prespore becomes a protoplast fully surrounded by the mother cell cytoplasm and separated from it by a double membrane system. Activation of G also requires expression of spoIIIJ, coding for a membrane protein translocase of the YidC/Oxa1p/Alb3 family, and of the mother cell-specific spoIIIA operon. Here we present genetic and biochemical evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 54 publications
(136 reference statements)
1
19
0
Order By: Relevance
“…Both proteins are essential for activation of a forespore-specific transcription factor and could be crosslinked in vivo. However, the level of membrane-inserted SpoIIIAE was not affected in a SpoIIIJ deletion strain (37), possibly suggesting a function in a postinsertional stage of SpoIIIAE biogenesis. Our report now demonstrates that both SpoIIIJ and YqjG mediate membrane insertion of in vitrosynthesized E. coli and B. subtilis F o c and supports the universal hypothesis that Oxa1p-like proteins are required for membrane insertion and biogenesis of subunits of respiratory chain complexes and other energy-transducing complexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both proteins are essential for activation of a forespore-specific transcription factor and could be crosslinked in vivo. However, the level of membrane-inserted SpoIIIAE was not affected in a SpoIIIJ deletion strain (37), possibly suggesting a function in a postinsertional stage of SpoIIIAE biogenesis. Our report now demonstrates that both SpoIIIJ and YqjG mediate membrane insertion of in vitrosynthesized E. coli and B. subtilis F o c and supports the universal hypothesis that Oxa1p-like proteins are required for membrane insertion and biogenesis of subunits of respiratory chain complexes and other energy-transducing complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a role for SpoIIIJ in membrane protein insertion was suggested based solely on its sequence similarity to E. coli YidC, although no direct experimental evidence for such a function was provided (4). Another report suggested that SpoIIIJ could be involved in the maturation of SpoIIIAE (37). Both proteins are essential for activation of a forespore-specific transcription factor and could be crosslinked in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The isolation of the forespore from the external milieu upon engulfment completion is a hallmark of endosporulation. A novel type of transport system coded for by the E -controlled spoIIIA operon allows the mother cell to feed the forespore, maintaining forespore-specific gene expression, when its engulfment is finalized (66,(104)(105)(106)(107). A central part of the complex is formed by the SpoIIIAH protein and by SpoIIQ, a F -controlled, forespore-specific protein, which interact directly across the intermembrane space, forming a channel that links the cytoplasm of the two cells (104)(105)(106)137).…”
Section: Discussionmentioning
confidence: 99%
“…Samples (0.6 ml) of DSM cultures were collected during sporulation and resuspended in 0.2 ml of phosphatebuffered saline, and the membrane dye FM4-64 (Molecular Probes) was added at a final concentration of 10 g ml Ϫ1 for visualization of membranes. Microscopy was carried out as described previously (66).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation